Logiciel SIG et pratique de terrain : quel positionnement de l’outil cartographique pour les acteurs du paysage ? - Sophie-Anne Olivier (Projets de Paysage)
This article looks at the landscape and fieldwork (in physical and social terms) and how the GIS as a tool can play a mediating role. How does it reconfigure our relationship with the land? How has the experience of fieldwork changed, both quantitatively and qualitatively? After taking stock of the experience of users in the field, this article shows how the use of a Geographic Information System (GIS) (and associated tools such as UAVs) creates a paradoxical distancing from the field and plays a mediating role. The project is based on two complementary types of materials. The first type is in the form of the proceedings of an online conference of users in 2020 (organised in four sessions on lessons learned followed by a panel discussion moderated by Thierry Joliveau) on the following theme: "Global Mapper, a field tool? Preparation, action and lessons learned". The event provided an opportunity to compare the views of professionals working on a wide range of subjects in which landscape studies play a central role: avalanche risk management, golf course mapping, notarial work and flight missions. The second type of material is a survey questionnaire aimed at GIS software users which attracted over 350 responses from users who do not do fieldwork and users who do. Among other things, this survey shows how certain tools (such as paper maps) are still in use, and how digital tools are both an invitation to engage in fieldwork and to depart from it.